A retrospective study of maternal near miss in the Critical Maternal Care Center in Suqian City, Jiangsu Province, China: A single‐center study. Issue 4 (14th October 2021) - Zhang, Shumin; Qi, Yalan; Xue, Xiumei; Zhang, Xiaojing; Cao, Qingling; Fang, Yuelan; Ge, Mingming
Abstract: Background and aims: Through a retrospective study of maternal near miss (MNM) cases treated by the Suqian Critical Maternal Care Center in Suqian City, Jiangsu Province, we summarized the most common diseases that caused MNM, treatment measures, and short‐term prognosis in this region. The purpose of the research is to improve the clinical evidence of maternal health care in the region. Methods: The study is a retrospective descriptive study. Among the pregnant women admitted to the Critical Maternal Care Center from 1 January 2015, to 31 December 2019, the pregnant women with severe pregnancy complications or comorbidities were identified as the research subjects. The study subjects were divided into an MNM group and a control group according to the MNM criteria recommended by the WHO. A retrospective analysis of the study subject data, including causes and clinical manifestations of MNM, treatment measures, and short‐term prognosis, was conducted. Results: The total number of deliveries was 27 619. There were 145 women in the control group and 65 women in the MNM group. The number of MNM cases accounted for 2.4% (65/27619) of the total number of deliveries. Placenta previa, postpartum hemorrhage, and hypertension accounted for 72.3% (47/65) of the causes of MNM cases observed. In the MNM group, the most common clinical manifestation was bleeding (80.0%, 52/65). Sixty‐three patients underwent massive blood transfusion (96.9%, 63/65), and 36 underwent hysterectomy (55.4%, 36/65). The prevalence of interventional procedures and unplanned secondary operations in the MNM group was higher than that in the control group. Conclusions: The top three causes of MNM were placenta previa, postpartum hemorrhage, and hypertension in pregnancy in Suqian area. Sufficient blood sources, convenient and fast blood transfusion procedures, and the use of large amounts of blood transfusion technology have an important impact on the success of treatment. Hysterectomy is still the main method of MNM treatment.